Multi-Criteria Frameworks to Improve Evaluation of the Effectiveness of Environmental Governance in the Amazon - Morales-Giner, Pilar; Speranza, Martina Laura; Arteaga, Marliz; Baudoin Farah, Andrea; Ferreira da Fonseca Junior, Sinomar; García Villacorta, Angélica; Rosero Peña, Martha; Perz, Stephen (Frontiers in Forests and Global Change, 2021)
In the Amazon, environmental governance (EG) is an important multi-stakeholder approach to the sustainable management of natural resources. There is by now a large theoretical literature on the many requirements for effective EG. There is also extensive empirical literature on EG in the Amazon. While empirical work in the Amazon has advanced our understanding of EG, it also has important limitations. There remains a need to unpack the many requirements for effective EG to identify violations of governance criteria to explain cases where EG is ineffective. There is also a need for multi-case comparative analyses of EG across diverse parts of the Amazon to identify common explanations for ineffective EG. Therefore, we review multi-criteria frameworks for the evaluation of EG, noting their contributions and differences. We draw on three recent frameworks for evaluating EG to suggest an integrated framework that can be applied to multiple cases for comparative evaluation. We argue that the use of an integrated framework for the identification of violations of specific criteria for effective EG can guide targeted conservation action. We then briefly discuss five study cases in the Amazon to outline how we could apply the integrated framework to identify unmet criteria to account for ineffective EG. We identify commonly unmet criteria for ineffective EG across the five cases. The identification of common criteria violated across cases can provide a basis for broader conservation strategies to improve EG.